Metallic Nanoparticles: A New Frontier in the Fight Against Leishmaniasis - Guerra, Rhanoica O.; do Carmo Neto, José Rodrigues; de Albuquerque Martins, Tarcísio; Farnesi de-Assunção, Thaís Soares; Junior, Virmondes Rodrigues; de Oliveira, Carlo José Freire; Silva, Anielle C. A.; da Silva, Marcos Vinicius (Current Medicinal Chemistry, 2022)
Leishmaniasis, a cutaneous, mucocutaneous, or visceral parasitic disease caused by the protozoa of the genus Leishmania, is responsible for approximately 20-40 thousand deaths annually, with Brazil, India, and certain countries in Africa being the most affected. In addition to the parasite’s ability to evade the host’s immune system, the incidence of vectors, genetics of different hosts, and several deaths are attributed to the limited conventional treatments that have high toxicity, low effectiveness, and prolonged therapeutic regimens. Thus, the development of new alternative therapeutic strategies remains warranted. Metallic nanoparticles, such as gold, silver, zinc oxide, and titanium dioxide, have shown promising therapeutic tools since they are easily prepared and chemically modified, have a broad spectrum of action and low toxicity, and can generate reactive oxygen species and other immune responses. This review explores the progress of the use of metallic nanoparticles as new tools in the treatment of leishmaniasis and discusses the gaps in knowledge hindering the development of a safe and effective therapeutic intervention against these infections.
Keywords: treatment